Determinants of Muslim’s intention to boycott Israel-affiliated products: Evidence from Indonesia - Husaeni, Uus Ahmad; Ayoob, Mohammed Ashfaq (Faculty of Economics, Universitas Islam Indonesia, 2025)
Purpose – The purpose of this study is to examine the factors that influence the intention to boycott products made or affiliated with Israel among Muslims in Indonesia. This study is grounded in the context of ongoing wars and conflicts in the Middle East, specifically in Palestine.Methodology – This research uses primary data collected from 412 respondents and the partial least squares structural equation model (PLS-SEM) method for data analysis.Findings – The main results show that animosity, intrinsic religious motivation, self-enhancement, product judgment, and attitude toward the boycott influence the intention to boycott. However, brand distrust does not determine the intention to boycott products affiliated with Israel.Implications – Indonesia is one of the largest markets for Muslims worldwide. Understanding the purchasing behavior of Muslim consumers in Indonesia can help marketers and multinational companies anticipate and strategically respond to potential boycotts, minimising financial losses. This is important because Muslim consumers in Indonesia often opt for alternative products when choosing to avoid those affiliated with Israel. Originality – Animosity was the most influential variable in this study. This reflects deep-seated resentment among Muslim consumers toward Israel, leading to a reluctance to purchase Israeli-affiliated products. They directly targeted Israeli-affiliated companies or products for boycotting as a form of expression of their anger and disapproval of Israel's invasion of Palestine. Interestingly, Muslim consumers in Indonesia still positively and favourably view products affiliated with Israel, even though they are reluctant to buy them.